Access to and governance of rural services: Agricultural extension and drinking water supply in Ethiopia - Mogues, Tewodaj; Cohen, Marc J.; Birner, Regina; Lemma, Mamusha; Randriamamonjy, Josee; Tadesse, Fanaye; Paulos, Zelekawork (International Food Policy Research Institute, 2009)
This study investigated access to agricultural extension and rural water supply and assessed strategies to improve the provision of these services by strengthening accountability. The study paid special attention to the gender dimension of service delivery. The research was conducted in eight districts located in seven administrative regions of Ethiopia, combining quantitative surveys with a qualitative case study approach. Empirical findings show that access to safe drinking water is rather low: 32% of the surveyed households use safe drinking water sources, and the average time to fetch water from safe sources during the dry season ranged from 29 minutes to 82 minutes. Agricultural extension services were relatively accessible, but there were differences in access between men and women, and particularly stark differences across the survey sites in different regions. Farmers' satisfaction with extension services was very high, but only 8 percent of the sampled farmers had adopted any new practices in the past two years.